CRISPR-Cas9-Based Technology and Its Relevance to Gene Editing in Parkinson's Disease - Mujeeb ur Rahman; Muhammad Bilal; Junaid Ali Shah; Ajeet Kaushik; Pierre-Louis Teissedre; Małgorzata Kujawska (MDPI AG, 2022)
Parkinson's disease (PD) and other chronic and debilitating neurodegenerative diseases (NDs) impose a substantial medical, emotional, and financial burden on individuals and society. The origin of PD is unknown due to a complex combination of hereditary and environmental risk factors. However, over the last several decades, a significant amount of available data from clinical and experimental studies has implicated neuroinflammation, oxidative stress, dysregulated protein degradation, and mitochondrial dysfunction as the primary causes of PD neurodegeneration. The new gene-editing techniques hold great promise for research and therapy of NDs, such as PD, for which there are currently no effective disease-modifying treatments. As a result, gene therapy may offer new treatment options, transforming our ability to treat this disease. We present a detailed overview of novel gene-editing delivery vehicles, which is essential for their successful implementation in both cutting-edge research and prospective therapeutics. Moreover, we review the most recent advancements in CRISPR-based applications and gene therapies for a better understanding of treating PD. We explore the benefits and drawbacks of using them for a range of gene-editing applications in the brain, emphasizing some fascinating possibilities.